How I Came to Sparkle Again : A Novel - McLaren, Kaya (New York : St. Martin's Press, 2012)
Three people in the ski town of Sparkle, Colorado, search for hope and love after painful losses, including a woman who discovered her husband's infidelity after a miscarriage, a woman whose best romantic prospect is a ski bum best friend, and a girl who longs for messages from her cancer victim mother.
Keywords: Self-realization -- Fiction